Über die Liebe oder Platons Gastmahl - Ficino, Marsilio 1433-1499; Hasse, Karl Paul; Blum, Paul Richard (Hamburg Meiner, 1984)
"De amore sive in convivium Platonis", the history of which extends well into the 17th century, is an adaptation and commentary on Plato in one and one of the most important philosophical works of the Renaissance.At a banquet ostensibly on the occasion of Plato's birthday, nine guests, all well-known Florentine scholars, present their views on love in alternating speeches, paraphrasing Plato's "Symposium" with a contemporary re-emphasis. The doctrine of amor / caritas becomes a speculative starting point for epistemology, theology, cosmology, ethics and natural philosophy.
Keywords: Plato -- 428/427-348/347 BC; 15th Century (1401-1500); Philosophy